Effect of Poultry Manure and Vertisols Matter on Availability and Leaching of Macronutrients in Coastal Sandy Soil - Purwantono, Anung Slamet Dwi; Indradewa, Didik; Sudira, Putu; Kertonegoro, Bambang Djadmo (JOURNAL OF TROPICAL SOILS, 2011)
The poultry manure and vertisols matter have potency for reclaiming a soil. The research objectives was to study the effect of poultry manure (PM) and vertisols matter (VM) on availability and leaching of macro nutrient in coastal sandy soil treated by rainfall simulation. A laboratory experiment was conducted with lesymeters to measure nutrient leaching. The factorial 4 Ã— 4 treatment applied was arranged by randomized completely block design with three replications. The first factor was level of PM consisted of 0, 20, 40, and 60 Mg ha-1. The second one wasthe level of VM consisted of 0, 5, 10, and 15%. Variables observed were soil physical and chemical properties such as bulk density (BD), particle density (PD), porosity, pF 2.54, pF 4.2, available water capacity (AWC), permeability, cation exchange capacity (CEC), available macro nutrients (N, P, K, Ca, Mg, and S) by Morgan Wolf extraction, and the rate of macro nutrient leaching measuared by Spectrophotometry and Atomic Absorption Spectrophotometry. Result of the research showed that application of PM and VM in the sandy soil decreased soil PD and BD, increased soil porosity and AWC, decreased soil permeability, and slightly increased soil CEC. Application of PM and VM increased soil available nutrient in the sandy soil. Up to 60 Mg ha-1 dose PM increased soil available nutrient, while 10 to 15% dose, VM did not increased it. The rank of nutrient leaching from high to low by rain simulation was N-NO3 -> SO4 = > K+ > Ca2+. Leaching of K and N-NH4+ could be reduced by soil amendment. Combination of PM 60 Mg ha-1 and VM 10% was the best soil amendment for increasing nutrient availability and decreasing nutrient leaching in the sandy soil.Keywords: available nutrient, coastal sandy soil, leaching, poultry manure, vertisols matter